GE_GERICHTE P/25121/2018 vom 24. November 2021 - GE Cour de justice (2021)
MENACE(DROIT PÉNAL);SÉJOUR ILLÉGAL;FIXATION DE LA PEINE;EXEMPTION DE PEINE;PEINE PÉCUNIAIRE | CP.180; LEI.115.al1; LEI.17.al1; CP.47; CP.49; CP.52; CP.54; CP.34.al1